2019
DOI: 10.3390/biomedicines7040091
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Admix Archaeal Glycolipid Adjuvanted Vaccine and Checkpoint Inhibitor Therapy Combination Enhances Protection from Murine Melanoma

Abstract: Archaeosomes are liposomes composed of natural or synthetic archaeal lipids that when used as adjuvants induce strong long-lasting humoral and cell-mediated immune responses against entrapped antigens. However, traditional entrapped archaeosome formulations have only low entrapment efficiency, therefore we have developed a novel admixed formulation which offers many advantages, including reduced loss of antigen, consistency of batch-to-batch production as well as providing the option to formulate the vaccine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
(75 reference statements)
0
20
0
Order By: Relevance
“…In this work we evaluated the protective capabilities of two new adjuvants: sulfated lactosyl archaeol (SLA) archaeosomes and AddaVax, a squalene-based oil-in-water emulsion similar to MF59. When used as an adjuvant, SLA has been shown to activate strong humoral and cell-mediated responses against multiple antigens by increasing local cytokine production, immune cell trafficking, and antigen uptake at the injection site, leading to increased protection in murine models of infectious disease and cancer (23)(24)(25). In this study, we used a novel admixed formulation which provides a simple ready to mix adjuvant formulation with no loss of antigen during the formulation process (26).…”
Section: Discussionmentioning
confidence: 99%
“…In this work we evaluated the protective capabilities of two new adjuvants: sulfated lactosyl archaeol (SLA) archaeosomes and AddaVax, a squalene-based oil-in-water emulsion similar to MF59. When used as an adjuvant, SLA has been shown to activate strong humoral and cell-mediated responses against multiple antigens by increasing local cytokine production, immune cell trafficking, and antigen uptake at the injection site, leading to increased protection in murine models of infectious disease and cancer (23)(24)(25). In this study, we used a novel admixed formulation which provides a simple ready to mix adjuvant formulation with no loss of antigen during the formulation process (26).…”
Section: Discussionmentioning
confidence: 99%
“…9 However, we have previously shown with our prime-boost vaccination strategy using a simplified SLA (Adm) formulation that exogenous antigens are similarly capable of inducing robust antigenspecific humoral/cell-mediated responses and tumor immunity as SLA (Enc) in vivo. 7,11 We show in the current study that even a single immunization with SLA (Adm) and (Enc) formulations with normalized lipid content (1,000 µg) can confer similar enhanced protection from B16-OVA melanoma tumor challenge. Whether the similarly enhanced protection conferred by SLA (Adm) and its SLA (Enc) counterpart can be partially attributed to cross-presentation by other specialized DC subsets in vivo remains to be elucidated.…”
Section: Discussionmentioning
confidence: 61%
“…Archaeosomes are prime adjuvant candidates due to their strong immunostimulatory properties, effective induction of humoral and cell-mediated immunity to numerous antigens and robust ability to confer protective immunity in multiple models of murine infection and cancer. 3,[5][6][7][8][9][10][11] Our novel SLAbased archaeosomes retain the robust adjuvant properties of traditional TPL formulations when antigen is encapsulated, while gaining the key advantage of a simplified semisynthetic single lipid formulation. Recently, we showed that admixing antigen with SLA offers increased consistency of antigen-to-lipid ratios and no antigen loss during formulation relative to antigen encapsulation, with no negative effect on the quality of antigen-specific responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Archaeosome-based formulations were able to protect immunized mice from multiple pathogens including Listeria monocytogenes , Trypanosoma cruzi and Mycobacterium tuberculosis , as well as to protect against solid and metastatic tumors in murine models [ 11 , 12 , 13 , 14 ]. More recently, we showed that a simplified archaeosome formulation composed of sulfated lactosyl archaeal (SLA) glycolipid can stimulate strong humoral and cell-mediated immune responses to multiple antigens in mice, including those targeting various infectious pathogens (influenza virus, Hepatitis B virus, Hepatitis C virus and Schistomiasis mansoni ) [ 15 , 16 , 17 , 18 ] or tumor types (breast cancer and melanoma) [ 19 , 20 ]. While originally used as delivery vehicles for encapsulated antigen, a simplified SLA formulation where antigens were simply admixed with pre-formed empty SLA vesicles was shown to generate equivalent or superior humoral and cell-mediated immune responses to conventional antigen-entrapped archaeosome formulations [ 21 ].…”
Section: Introductionmentioning
confidence: 99%